2014
DOI: 10.1016/j.tiv.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of xylazine on endothelial cells in combination with cocaine and 6-monoacetylmorphine

Abstract: The use of xylazine as a drug of abuse has emerged worldwide in the last 7 years, including Puerto Rico. Clinical findings reported that xylazine users present greater physiological deterioration, than heroin users. The aim of this study was to assess the xylazine toxicity on endothelial cells, as this is one of the first tissues impact upon administration. Human umbilical vein endothelial cells in culture were treated with xylazine, cocaine, 6-monoacetylmorphine (heroin metabolite) and its combinations, at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…The results of the experiment corroborate those of other studies which showed that xylazine is toxic to thymocytes (CUPIĆ et al, 2003), splenocytes (CUPIĆ et al, 2001), chondrocytes (MANCINI et al, 2017), mesenchymal cells (EDMONDS et al, 2016) and endothelial cells (SILVA-TORRES et al, 2014). Mancini et al (2017) assessed the cell morphology of chondrocytes treated with xylazine using cell cytometry and verified cell death due to apoptosis.…”
Section: Resultssupporting
confidence: 85%
“…The results of the experiment corroborate those of other studies which showed that xylazine is toxic to thymocytes (CUPIĆ et al, 2003), splenocytes (CUPIĆ et al, 2001), chondrocytes (MANCINI et al, 2017), mesenchymal cells (EDMONDS et al, 2016) and endothelial cells (SILVA-TORRES et al, 2014). Mancini et al (2017) assessed the cell morphology of chondrocytes treated with xylazine using cell cytometry and verified cell death due to apoptosis.…”
Section: Resultssupporting
confidence: 85%
“… 15 However, the toxic effects of xylazine in combination with heroin and/or cocaine or other drugs in humans have remained unexplored due to the restriction of its administration to humans. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…The effects of xylazine could be attenuated, blocked, and reversed with the α2-adrenergic antagonist yohimbine . In the past decade, xylazine became a popular recreational drug worldwide , and has been widely used to adulterate illicit drugs such as cocaine, heroin, and speedball (a mixture of cocaine and heroin) . However, the toxic effects of xylazine in combination with heroin and/or cocaine or other drugs in humans have remained unexplored due to the restriction of its administration to humans. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated XYL use alone or in combination with COC and/or 6-MAM diminished proliferation and induced apoptosis in EA.hy926 cells (HUVEC) [ 25 ]. This apoptosis process could be triggered by increased production of nitrogen and oxygen reactive species.…”
Section: Introductionmentioning
confidence: 99%